The irrelevant speech effect among younger and older adults: The influence of background noises on reading comprehension. Issue 2 (15th March 2018) - Murphy, Dana R.; Bailey, Helen; Pearson, Marlena; Albert, Graham
ABSTRACT: Background : Aging could exacerbate the decreases in cognitive functioning already caused by noise pollution. According to the inhibitory deficit hypothesis, older adults have more difficulty than do younger adults keeping irrelevant information from interfering with processing of relevant information. However, irrelevant speech studies typically fail to support this hypothesis. The present study aimed to quantify the effects of age and noise pollution on reading comprehension. Methods : Seventeen younger (age 21–29) and 15 older (age 62–77) adults completed a reading task (reading discourse material for a follow-up comprehension test) in the presence of six irrelevant background noise conditions. Repeated measures ANOVAs and t tests were used to analyze participant accuracy on the follow-up comprehension tests. Results : Contrary to the inhibitory deficit hypothesis, but congruent with previous irrelevant speech studies, younger and older adults did not have significantly different reading comprehension scores, and both groups' accuracy was greatest when asked to read in silence. Noise conditions that contained English speech, regardless of whether this background noise was spoken or sung, were most disruptive. Conclusion : Younger and older adults appear to be equally influenced by irrelevant background material when reading. Regardless of age, reading in a distraction-free environment whenever possible is the best way to maximize reading comprehension.